2022
DOI: 10.1136/bmjgast-2022-001016
|View full text |Cite
|
Sign up to set email alerts
|

Variables associated with progression of moderate-to-severe Crohn’s disease

Abstract: ObjectiveDetermine the variables associated with hospitalisations in patients with Crohn’s disease and those associated with surgery, intestinal resection, hospital readmission, need for multiple operations and immunobiological agent use.DesignA cross-sectional study was conducted from 2019 to 2021, using two centres for inflammatory bowel diseases in the Brazilian Public Health System.ResultsThis study included 220 patients. Only perianal disease was associated with hospitalisation (31.6% vs 13.0%, p=0.012). … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Romberg-Camps et al 36 showed that in CD, small bowel location, stricturing disease, and young age predicted disease recurrence, whereas in UC, extensive colitis and older age at diagnosis were negative prognostic predictors. Recently, Sacramento et al 37 reported the variables associated with moderate-to-severe CD progression. These results are also in line with our findings, demonstrating perianal disease, stricturing or penetrating behavior, and ileocolonic localization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Romberg-Camps et al 36 showed that in CD, small bowel location, stricturing disease, and young age predicted disease recurrence, whereas in UC, extensive colitis and older age at diagnosis were negative prognostic predictors. Recently, Sacramento et al 37 reported the variables associated with moderate-to-severe CD progression. These results are also in line with our findings, demonstrating perianal disease, stricturing or penetrating behavior, and ileocolonic localization.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients from private services, only those with moderate-to-severe CD had access to anti-TNFs, anti-integrins, and anti-interleukins. The publication of national epidemiological studies 2,3,5,[30][31][32][33]37,[44][45][46][47][48] , physicians´ perceptions of IBD in Brazil 43 , and studies on the socioeconomic impact of IBD, including absence from work 27,49,50 , served to alert the authorities and resulted in the incorporation of biological therapy for UC in the public sphere in 2020 and in the private system in 2021.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors have been identified for Crohn's disease patients at high-risk for complications, surgery, hospitalization, and disability. These include clinical factors (onset <40 years of age, perianal disease, presence of fistula, presence of strictures, prior intestinal resection, active small bowel disease, active smoking, systemic corticosteroid, and prior advanced therapy failure), endoscopic and radiologic factors (large and deep ulcerations, ileal involvement >40 cm, and pancolitis), as well as laboratory factors (anemia, elevated CRP, and low albumin) [91,95,96].…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%